Cognition and physical functioning in patients with schizophrenia: any role for vitamin D? - Azar, Jocelyne (2019)
Aim: The study’s objective was to evaluate the relationship between vitamin D (VD) levels and cognitive performance in patients with schizophrenia. Methods: A cross-sectional study, conducted between March and July 2016, recruited 196 patients with schizophrenia. The Brief Cognitive Rating Scale (BCRS) and the Morningside Rehabilitation Status Scale (MRSS) were used to measure the severity of cognitive impairment and the level of general functioning in psychiatric patients. Lower scores for both scales indicate a better cognition and functioning respectively. Vitamin D levels of participants were divided into four groups: severe VD deficiency (<10 ng/ml), VD deficiency (10–20 ng/ml), VD insufficiency (20–30 ng/ml), VD sufficiency (>30 ng/ml). Relationships between VD level and cognition and functioning were assessed by analyses of covariance and hierarchical multiple regression, adjusted for age, gender, marital status, education level, sun exposure, physical activity and monthly income. Results: Severe VD deficiency was found in 22 patients with schizophrenia (11.3%), while 45.6% of patients had VD deficiency. Severe VD deficiency was significantly associated with an increase in MRSS score after adjusting for covariates (Beta = 2.44), however, no significant association was found with the BCRS score. Conclusion: These findings suggest that severe VD deficiency in patients with schizophrenia might be associated with low general functioning but could not influence cognitive function.